2002
DOI: 10.1051/vetres:2002027
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk fat globules do not inhibit C5a chemotactic activity

Abstract: -The C5a complement fragment is a potent inflammatory molecule but its contribution to the inflammatory response of the mammary gland remains uncertain. One of the unresolved questions is the possible interference of whole milk with C5a. In this study, the chemotactic activity of purified bovine C5a was tested in the presence of whole or skimmed milk. Milk from healthy glands acted as a chemoattractant, which could mask any inhibitory effect on C5a activity. To circumvent milk activity, washed milk fat globule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This result indicates that the components of whole milk inhibit the inflammatory activity of ZAP. One simple assumption is that the milk fat globules interfered with the inflammatory activity of C5a, but the investigations with bovine milk fat globules and purified bovine C5a showed that fat globules do not trap or inactivate C5a [84]. Whatever the underlying mechanism, the inhibition of the C5a recruiting activity by whole milk casts doubt on the contribution of the intrinsic milk complement in the initiation of the inflammatory reaction of the lactating mammary gland.…”
Section: Recruitment Of Phagocytesmentioning
confidence: 99%
“…This result indicates that the components of whole milk inhibit the inflammatory activity of ZAP. One simple assumption is that the milk fat globules interfered with the inflammatory activity of C5a, but the investigations with bovine milk fat globules and purified bovine C5a showed that fat globules do not trap or inactivate C5a [84]. Whatever the underlying mechanism, the inhibition of the C5a recruiting activity by whole milk casts doubt on the contribution of the intrinsic milk complement in the initiation of the inflammatory reaction of the lactating mammary gland.…”
Section: Recruitment Of Phagocytesmentioning
confidence: 99%
“…They include increased mammary blood flow facilitating delivery of neutrophils, complement factors and chemotactic factors to the gland stabilization and attenuation of bacterial toxin-related apoptosis, counter-regulation of adverse proinflammatory cytokine release, and facilitated augmentation of growth factor production including IGF-1 [38,43,[45][46][47][48]. Exactly how AM affects the biological activity of AM-BP towards processing of complement C3 and the progression through the complement cascade towards complement C5-mediated chemotactic attraction of monocytes, granulocytes and neutrophils [49] to sites of mammary infection remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Pio et al [17] demonstrated that the minimal inhibitory concentration of AM effective against E. coli shifted from 10 to more than 35 g/ml when AM was complexed with AM-BP. Interestingly, the activity of AM-BP as complement factor-H (responsible cofactor for the factor I-dependant cleaving of complement C3B) is increased when AM is bound [17] suggesting that aspects of the innate complement cascade within the mammary gland [49] are also modulated by AM. Furthermore, increased beneficial clinical outcome (decreased morbidity and mortality) recently has been attributed to the use of an AM/AM-BP complex as an intervention strategy to limit the complicating effects of sepsis and hypovolumic shock on progression into multiple organ failure [19,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of blood and postdiapedetic PMN functions and concentrations in different physiological and pathological conditions remains the focus of most concern. Although the presence of strong chemotactic factors in non-inflamed udder is the subject of debate, their presence in inflammatory environment of udder and milk is indisputable (Manlongat et al, 1998;Rainard, 2002;Stevens et al, 2011a;2011b;Pezeshki et al, 2011). Most inflammatory chemoattractants are only induced and released during acute infection.…”
Section: Movement Of Neutrophils From Bone Marrow To the Mammary Glandsmentioning
confidence: 99%
“…Neutrophils engage microorganisms through extracellular membrane receptors like PRRs, e.g., TLRs, C-type lectins (mannose receptor), scavenger receptors like CD36, Nod-like receptors (NLRs), and N-formyl Met-Leu-Phe (f-MLP) receptors (Nathan., 2006;Diez-Fraille et al, 2004;Bellocchio et al, 2004;Sohn et al, 2007a;2007b ;Zarbock A & Ley, 2008;Rainard, 2002;Stevens et al, 2011a;2011b). Neutrophils also bind to pathogens coated with various opsonins like IgG, complement components (e.g.…”
Section: Movement Of Neutrophils From Bone Marrow To the Mammary Glandsmentioning
confidence: 99%